2022
DOI: 10.3390/su14137707
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Placement and Operation of FACTS Technologies in a Cyber-Physical Power System: Critical Review and Future Outlook

Abstract: With the current transitioning and increasing complexity of power systems owing to the continuous integration of distributed generators (DGs) and Flexible AC Transmission Systems (FACTS), power system quality and security studies have extended to incorporate the impacts of these technologies. This paper presents a review of the operation and reliability impacts of FACTS technologies in improving power quality and security in modern Cyber-Physical Power Systems (CPPS). While introducing DG to the power system h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 123 publications
0
6
0
Order By: Relevance
“…These risks can jeopardize power system safety and reliability, resulting in power outages, revenue loss, and damage to critical infrastructure. To ensure the safe and secure deployment of AI and IoT in the power sector, it is critical to understand the industry's current state of AI and cybersecurity, as well as identify and address major threats and challenges [6]. AI and IoT systems generate massive amounts of data, increasing the vulnerability to cyberattacks.…”
Section: ░ 2 Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…These risks can jeopardize power system safety and reliability, resulting in power outages, revenue loss, and damage to critical infrastructure. To ensure the safe and secure deployment of AI and IoT in the power sector, it is critical to understand the industry's current state of AI and cybersecurity, as well as identify and address major threats and challenges [6]. AI and IoT systems generate massive amounts of data, increasing the vulnerability to cyberattacks.…”
Section: ░ 2 Backgroundmentioning
confidence: 99%
“…These studies sought to address the major challenges and opportunities in the field of artificial intelligence and cybersecurity in the power sector. A substantial body of literature has focused on the major threats and challenges to power system cybersecurity in the age of AI and IoT [6]. These studies have identified a variety of potential cyber-attacks, including data breaches, unauthorized access, and critical system manipulation [8].…”
Section: ░ 3 Literature Reviewmentioning
confidence: 99%
“…It was in 2018 the authors (Venkateswarlu et al, 2018) reviewed the applications of VSC, a subsynchronous damping controller for damping torsional interactions in power systems. In 2020 the allocation of FACTS devices in power systems using metaheuristic optimisation techniques was reviewed by Okampo, Nwulu and Bokoro (2022). In 2020 a review on improving the power performance using FACTS was presented in Singh and Kumar (2020).…”
Section: Voltage Stability In Power Systemmentioning
confidence: 99%
“…Local and coordinated control was applied to mitigate the voltage violation in the DN with high penetration of the DGs [54]. The optimal allocation and operation of the flexible AC transmission systems (FACTs) in the cyber-physical DN-based IoT communication platform was discussed in [55].…”
Section: Introductionmentioning
confidence: 99%